PD-1/PD-L1 axis in organ fibrosis - Zhao, Youliang; Qu, Yaqian; Hao, Changfu; Yao, Wu (Frontiers in Immunology, 2023)
Fibrosis is a pathological tissue repair activity in which many myofibroblasts are activated and extracellular matrix are excessively accumulated, leading to the formation of permanent scars and finally organ failure. A variety of organs, including the lung, liver, kidney, heart, and skin, can undergo fibrosis under the stimulation of various exogenous or endogenous pathogenic factors. At present, the pathogenesis of fibrosis is still not fully elucidated, but it is known that the immune system plays a key role in the initiation and progression of fibrosis. Immune checkpoint molecules are key regulators to maintain immune tolerance and homeostasis, among which the programmed cell death protein 1/programmed death ligand 1 (PD-1/PD-L1) axis has attracted much attention. The exciting achievements of tumor immunotherapy targeting PD-1/PD-L1 provide new insights into its use as a therapeutic target for other diseases. In recent years, the role of PD-1/PD-L1 axis in fibrosis has been preliminarily explored, further confirming the close relationship among PD-1/PD-L1 signaling, immune regulation, and fibrosis. This review discusses the structure, expression, function, and regulatory mechanism of PD-1 and PD-L1, and summarizes the research progress of PD-1/PD-L1 signaling in fibrotic diseases.